Diversity of SNP c.795A>G PLAG1 Gene and its Association to Birth Weight of Bali Cattle - Adefia Fahira; Ronny Rachman Noor; Jakaria Jakaria (Indonesian Center for Animal Research and Development (ICARD), 2022)
PLAG1 gene is one of those that regulate growth and body size. This study aimedto look at the PLAG1 gene polymorphism and its relationship to birth weight in Bali cattle using PCR-RFLP. The total sample used was 104 samples consisting of 66 Bali cattle from BPTU-HPT Denpasar and 38 Bali cattle from BPT-HMT Serading, each of which had birth weight data. PLAG1 gene polymorphism was analyzed using PCR-RFLP and the Sac1 restriction enzyme. The genotype and allele frequencies, heterozygosity, and Hardy-Weinberg equilibrium were all examined using Popgen32. General Linear Model was used to analyze the association of SNP 795AG PLAG1 gene with birth weight in Bali cattle. Amplification of the PLAG1 gene resulted in 776 bp fragments and two alleles. The PLAG1 gene had three genotypes: AA (562 bp and 182 bp), AG (562 bp, 182 bp, and 104 bp), and GG (562 bp, 182 bp, and 104 bp). Based on the results, the PLAG1 gene in Bali cattle was polymorphic. The alleles frequency of Bali cattle wasin Hardy-Weinberg equilibrium. The SNP c.795AG PLAG1 gene genotype were associated with birth weight in Bali cattle. The A allele is a determinant of high birth weight in Bali cattle where the AG genotype has the highest birth weight.